Revalidation of the two upogebiid mud shrimp species, Upogebia foresti Ngoc-Ho, 1989 and Upogebia rupicola Komai, 2005, removed from the synonymy of Upogebia carinicauda (Stimpson, 1860) (Decapoda: Gebiidea) - Komai, Tomoyuki; Fujita, Yoshihisa (Zootaxa, 2026)
Analysis of morphological data and genetic data from two mitochondrial markers, cytochrome c oxidase subunit 1 (COI) and 16S rRNA genes, has revealed that three species are mixed up within the material from the Ryukyu Islands, Japan, and can be identified as Upogebia carinicauda (Stimpson, 1860) (type locality: Hong Kong) according to the latest classification. This finding led to the revalidation of U. foresti Ngoc-Ho, 1989 (type locality: Koepang, Timor, Indonesia) and U. rupicola Komai, 2005 (type locality: Okinawa Island, Ryukyu Islands), which were previously considered junior synonyms of U. carinicauda. Updated descriptions of U. carinicauda and U. foresti are provided based on the current material. The distinguishing features among U. carinicauda, U. foresti, and U. rupicola are re-evaluated. A comprehensive review of previous records of U. carinicauda and the reassessment of the status of the closely related U. kempi Shenoy, 1967 (type locality: Bombay, India), are deferred due to difficulties in accessing the voucher specimens. Additionally, a brief overview of the Japanese species of Upogebia Leach, 1814, is included. Currently, 14 species of this genus are recognized in the Japanese marine fauna.